2015
DOI: 10.1016/j.engfracmech.2015.03.026
|View full text |Cite
|
Sign up to set email alerts
|

The effects of notch size and material microstructure on the notch sensitivity factor for notched components

Abstract: Keywords:Nickel base superalloy Non-metallic inclusions Probabilistic framework Fatigue notch factor Crystal plasticity a b s t r a c t Nickel base superalloys are used in hot sections of gas turbine engines due to its high strength and good creep, fatigue, and corrosion resistance at high temperature. In this paper, a new probabilistic approach based on weakest-link theory that accounts for the effects of the microstructure, notch size and notch acuity is described and applied to nickel base superalloy to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…While Karry and Dolan provide a formula for the dependency of the fatigue notch factor k f on grain size in brass specimens [32], a robust relation between grain size and the notch support parameters A and k for the geometry independent notch support factor n χ is yet to be found. Note that A and k are single values and not explicitly considered to be statistically distributed as k f in [17] for example. Instead, all additional data scatter emanating from the notch support effect is covered by the Weibull shape parameter m during the model calibration.…”
Section: Comparison Of Notch Support Mechanism In Different Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…While Karry and Dolan provide a formula for the dependency of the fatigue notch factor k f on grain size in brass specimens [32], a robust relation between grain size and the notch support parameters A and k for the geometry independent notch support factor n χ is yet to be found. Note that A and k are single values and not explicitly considered to be statistically distributed as k f in [17] for example. Instead, all additional data scatter emanating from the notch support effect is covered by the Weibull shape parameter m during the model calibration.…”
Section: Comparison Of Notch Support Mechanism In Different Materialsmentioning
confidence: 99%
“…Another probabilistic approach to notch support is presented in [16] and [17], for example where fatigue notch factors for high cycle fatigue (HCF) based on the random distribution of failure inducing defects in the material are computed. Hertel et al already take into account a macro support factor which combines the statistical size effect and geometrical support effects [18].…”
Section: Introductionmentioning
confidence: 99%
“…The equations that model these finite elements are assembled into a system of equations that models the entire problem. The FEA application covers a wide range of engineering and scientific problems [18][19][20][21]. Owolabi et al studied the notch root radius effect on the probability of failure [18].…”
Section: Introductionmentioning
confidence: 99%
“…The FEA application covers a wide range of engineering and scientific problems [18][19][20][21]. Owolabi et al studied the notch root radius effect on the probability of failure [18]. Chaves et al correlated the stress gradient at the notch obtained through FEA to the fatigue behavior [19].…”
Section: Introductionmentioning
confidence: 99%
“…Many authors studied the influence of notch size and geometry on different alloys strength. Owolabi et al [15] studied the influence of notch size and material microstructure on notch sensitivity for an IN 100 superalloy. They simulated a probabilistic 2 of 24 mesomechanics model and compared it with experimental results and concluded that the probability of failure, fatigue notch factor and associated notch sensitivity index increases with the increasing notch root radius.…”
Section: Introductionmentioning
confidence: 99%